The age of reform (Filmstrip) - Yale University. Press. Film Service. [from old catalog] (Yale University Press Film Service, 1954)
Presents a survey of the economic, social, and political changes which took place in the United States between 1880 and 1912. Explains that the vast industrial developments after the Civil War precipitated social, economic, and political problems. Describes the various reforms which took place during the administrations of Presidents Arthur, Cleveland, Harrison, McKinley, Roosevelt, and Taft. Captioned photographs.
With teacher's guide, by William H. Hartley.
Correlated with The pageant of America, edited by R. H. Gabriel.
CREDITS: Editors, Ralph H. Gabriel, William H. Hartley, Clyde M. Hill, May Hall James.
Keywords: United States -- History -- 1865-